2007
DOI: 10.1146/annurev.nutr.25.050304.092545
|View full text |Cite
|
Sign up to set email alerts
|

Role of Dietary Proteins and Amino Acids in the Pathogenesis of Insulin Resistance

Abstract: Dietary proteins and amino acids are important modulators of glucose metabolism and insulin sensitivity. Although high intake of dietary proteins has positive effects on energy homeostasis by inducing satiety and possibly increasing energy expenditure, it has detrimental effects on glucose homeostasis by promoting insulin resistance and increasing gluconeogenesis. Varying the quality rather than the quantity of proteins has been shown to modulate insulin resistance induced by Western diets and has revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
215
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(224 citation statements)
references
References 160 publications
7
215
2
Order By: Relevance
“…Most recently, it has been reported that branched-chain amino acids in diet contribute to insulin resistance in high fat diet-fed rats and that a similar consequence of such a dietary pattern may exist in human (10). Currently, a role of dietary proteins in the pathogenesis of insulin resistance has been well recognized (11), but the underlying molecular mechanisms are not yet fully understood.…”
mentioning
confidence: 99%
“…Most recently, it has been reported that branched-chain amino acids in diet contribute to insulin resistance in high fat diet-fed rats and that a similar consequence of such a dietary pattern may exist in human (10). Currently, a role of dietary proteins in the pathogenesis of insulin resistance has been well recognized (11), but the underlying molecular mechanisms are not yet fully understood.…”
mentioning
confidence: 99%
“…Due to the high prevalence of diabetes worldwide, extensive research is still being performed to develop new antidiabetic agents (ADA 2007;Venkateswaran and Pari 2003;Udayakumar et al 2009;Samane et al 2006;Luo and Luo 2006). Modulating dietary proteins and the flux of circulating amino acids generated by their consumption and digestion might underlie powerful new approaches to treat various metabolic diseases such as obesity and diabetes (Tremblay et al 2007;Wu 2009). Previously we have reported the hypoglycemic effect of CKP in alloxan treated rats, but its effect on nitric oxide pathway and RAGE was unknown.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro and in vivo findings indicate an important role of amino acids in glucose homeostasis through inhibition of insulin action on muscle glucose transport and hepatic glucose production. This negative effect of amino acids on insulin action appears to be associated with mTOR/S6K1-dependent inhibitory phosphorylation of insulin receptor substrate-1 (IRS-1) on serine and/or threonine residues and impaired activation of PI3K, a key effector of the metabolic actions of insulin (Tremblay et al, 2007;Um et al, 2006). Depletion of S6K1 was recently shown to enhance basal glucose utilization in mammalian muscle cells and to protect against the development of impaired insulin action in response to excessive leucine (Deshmukh et al, 2009).…”
Section: Atrogin-1 Murf1mentioning
confidence: 99%